The Role Of Neuro-Imaging Techniques In Prediction Of Stroke - Maharishi, R.; Rathnasabapathy, Maya (International Journal of Engineering and Technology, 2018)
At present there are many techniques and methods are used to measuring brain injuries or functions of the brain in the modern medicine scenario. A critical goal of this research study is that the stroke has classified the location and volume of the lesion for treatment. In the stroke assessment most commonly used brain imaging techniques are administered to evaluate the position of pathology and its functions. Any types of stroke it may be it will be assessed based on the Neuro-imaging methods like Computerized Tomography (CT scan), Magnetic Resonance Imaging (MRI scan), Functional Magnetic Resonance Imaging (fMRI), Electroencephalography (EEG), Tissue Plasminogen Activator (Tpa), Transcranial Magnetic Stimulation (TMS).Â  These neuroimaging techniques are excellent technical development to the current state wherein these methods provide physiological information highly relevant to the stroke patient. And also the study is exploring how the neuroimaging techniques are making a significant impact on the neuropsychological functions of stroke patients.Â